2009
DOI: 10.1007/s12648-009-0062-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of seasonal variation of indoor radon concentration in Tehri Garhwal, Northern India

Abstract: The seasonal variation analysis of indoor radon has been carried out in the hilly region of Tehri Garhwal, Northern India by using LR-115 Type II, plastic track detector. In the analysis the winter/summer ratio radon values were found to vary from 0.63 to 1.64 and 1.02 to 1.22 for cemented houses and mud houses, respectively. Over all the average value of winter/summer ratio was found maximum in both cemented and mud houses respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 2 publications
0
3
1
Order By: Relevance
“…In Table 4, a comparison of winter to summer ratio of indoor radon observed in present study with the literature reports has been discussed. The winter to summer ratio of indoor radon of Muktsar, Ferozpur 22 and Malwa region of Punjab 23 , Western Haryana of India 24 , Kullu area of Himachal Pradesh 19 , Tehri Garwal of Uttarakhand 25 , Sikar and Churu district of Northern Rajasthan 26 , India is lower than the present investigated values.…”
Section: Resultscontrasting
confidence: 76%
“…In Table 4, a comparison of winter to summer ratio of indoor radon observed in present study with the literature reports has been discussed. The winter to summer ratio of indoor radon of Muktsar, Ferozpur 22 and Malwa region of Punjab 23 , Western Haryana of India 24 , Kullu area of Himachal Pradesh 19 , Tehri Garwal of Uttarakhand 25 , Sikar and Churu district of Northern Rajasthan 26 , India is lower than the present investigated values.…”
Section: Resultscontrasting
confidence: 76%
“…Kansal et al 8 reported winter to summer ratio of indoor radon in the range of 0.78-2.99 with an average of 1.52 in the Western Haryana, India. The winter to summer ratio of indoor radon in Kullu area of Himachal Pradesh, India lies in the range of 1.08-1.96 with an average of 1.54 as reported by Singh et al 20 Kandari and Ramola 28 reported winter to summer ratio of indoor radon in the range of 0.63-1.64 with an average of 1.16 in the Tehri Garhwal region of Northern India. Rani et al 29 reported winter to summer ratio of indoor radon in the range of 1.15-1.62 with an average of 1.31 in the Punjab and Himachal Pradesh states of India.…”
Section: Resultsmentioning
confidence: 72%
“…Kandari and Ramola 28 reported winter to summer ratio of indoor radon in the range of 0.63–1.64 with an average of 1.16 in the Tehri Garhwal region of Northern India. Rani et al.…”
Section: Resultsmentioning
confidence: 99%
“…Wayanad is one of the coldest high range tourist places situated in the Western Ghats of southern India. Several studies have proved the increase in the concentration of indoor radon with decreasing temperature [ 10 12 ]. These studies have reported indoor radon thoron levels which are higher than those seen in the High Natural Background Radioactivity Areas (HNBRA) of Kerala.…”
Section: Introductionmentioning
confidence: 99%